Dampak Penerapan Model Pembelajaran Index Card Match (ICM) Terhadap Pemahaman Konsep Matematika Barisan dan Deret Aritmetika - Mamonto, Putri Yanti; Ismail, Sumarno; Isa, Dewi Rahmawaty (Research in the Mathematical and Natural Sciences, 2024)
Learning mathematics requires students to understand concepts, the low understanding of students' concepts becomes an obstacle in learning. So that the researchers used the background to apply the Index Card Match (ICM) learning model. This study aims to improve understanding of mathematical concepts using the Index Card Match (ICM) learning model on arithmetic sequences and series material. This research is a classroom action research. The research subjects were students of class XI TKJ SMK Negeri 1 Batudaa for the academic year 2022/2023 with a total of 28 students. The techniques used in data collection are observation and tests. The data analysis technique in this study is the analysis of observation of teacher activities, student activities and tests of understanding mathematical concepts. The design used in this study is the research design of the Kammis and Mc Taggart models. The research procedure includes planning, implementation, observation and reflection. The study consisted of 2 cycles. The results showed that the implementation of learning using the Index Card Match learning model on arithmetic sequences and series materials could improve students' understanding of mathematical concepts. This is evidenced by the average results of the mathematical concept understanding test in the first cycle which is 63.57, increasing in the second cycle to 81.42 with the percentage of observations of teacher activities in the first cycle reaching 71.15% while the second cycle reaches 86.53% and the percentage the results of the observation of student activity in the first cycle reached 65.17%, an increase in the second cycle reached 83.92%. Based on the research above, there are benefits in applying the Index Card Match (ICM) learning model, namely, in order to increase understanding of mathematical concepts and foster motivation and interest in learning mathematics.